PENGARUH STRATEGI BISNIS PERUSAHAAN DAN KOMPETISI PASAR EKUITAS TERHADAP RISIKO CRASH HARGA SAHAM DENGAN OVERVALUED EQUITIES SEBAGAI VARIABEL MEDIASI - Fidya Gumilang Arianwuri; Sutrisno T; Yeney Widya Prihatiningtyas (Universitas Muhammadiyah Malang, 2017)
Business Strategy, Equity Market Competition, Overvalued Equities, and Stock Price CrashRisk. The purpose of this research is to examine the influence of prospector business strategyand defender business strategy, equity market competition, and indirect effect of prospectorbusiness strategy on stock price crash risk through ovevalued equities. The sample of thisresearch are 192 companies that are divided into 96 prospector business strategy and 96 defender business strategy during 2010-2016. This study uses a secondary data from financialreport, number of investor, and stock price information. Which is obtained from the officialwebsite of IDX, KSEI and yahoo finance. The results of this study indicate that the prospectorbusiness strategy effect on the stock price crash risk, while the defender business strategy doesnot affect on stock price crash risk. The equity market competition is proven to reduce the stockprice crash risk. The existence of a prospector business strategy will tend to overvalued equitieswhich in turn, increase stock price crash risk.Ke ywords: defender business strategy, equity market competition, overvalued equities, prospector business strategy, stock price crash risk